2021
DOI: 10.1094/phyto-03-21-0083-r
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Root Rot Complex in Soybean: Molecular Characterization, Trichothecene Formation, and Cross-Pathogenicity

Abstract: Soybean is threatened by many pathogens that negatively affect this crop's yield and quality, e.g., different Fusarium species that cause wilting and root rot diseases. Fusarium root rot (FRR) in soybean can be caused by F. graminearum and other Fusarium spp. that are associated with Fusarium head blight (FHB) in cereals. Therefore, it was important to enquire whether Fusarium pathogens from soybean can cause disease in wheat, and vice versa. Here, we investigated the Fusarium root rot complex in Manitoba (Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 126 publications
3
37
1
Order By: Relevance
“…F. oxysporum was found to be the most severe species in terms of its impact on plant growth, indicating that it is the most aggressive isolate. These findings are consistent with previous studies that have shown F. oxysporum and F. solani to be highly virulent pathogens that can cause significant yield losses in soybean ( Hafez et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
“…F. oxysporum was found to be the most severe species in terms of its impact on plant growth, indicating that it is the most aggressive isolate. These findings are consistent with previous studies that have shown F. oxysporum and F. solani to be highly virulent pathogens that can cause significant yield losses in soybean ( Hafez et al, 2021 ).…”
Section: Resultssupporting
confidence: 93%
“…Notably, Fusarium also showed prominent pathogenicity against the host, causing a series of diseases that reduced host growth. As previously described by Hafez et al [ 54 ], Fusarium can affect soybean, resulting in Fusarium root rot. In addition, Fusarium may also be the causal agent of mango leaf spots [ 55 ].…”
Section: Discussionmentioning
confidence: 81%
“…The other two species included in our research, F. culmorum and F. redolens , have been rarely studied in the context of their pathogenicity on soybean seedlings. F. culmorum was found to be pathogenic for soybean in Canada [ 50 , 55 ]. Although, Zeng et al [ 23 ] describe this species as one of the major causal agents of soybean root rot in three provinces in China.…”
Section: Discussionmentioning
confidence: 99%